Efficacy comparison of optimal natural orifice specimen extraction for robotic middle rectal cancer resection in women: transanal or transvaginal orifice - Yao Yao; Jiarui Ding; Houqiong Ju; Lingling Yang; Yang Liu; Yahang Liang; Yuli Yuan; Taiyuan Li; Xiong Lei (World Journal of Surgical Oncology)
Abstract Purpose This study aimed to determine the optimal natural orifice specimen extraction (NOSE) method for robotic-assisted mid-rectal cancer resection in women. Methods This retrospective propensity score-matched (PSM) study was to analyze the clinical data prospectively collected from female rectal cancer patients who underwent either robotic-assisted transvaginal specimen extraction (RATV) or robotic-assisted transanal specimen extraction (RATA) at our center between June 2016 and December 2022. The main outcome measures were urinary, anal, and sexual function. Disease-free survival (DFS), and overall survival (OS) were also included . Results Anal function, assessed by the Wexner score, was better in the RATV group than in the RATA group (P = 0.034). Additionally, pre-menopausal women in RATV group exhibited superior anal function over those in RATA group (P = 0.031). There was no statistically significant difference in urinary function between the groups for both pre-menopausal and peri-menopausal patients (P = 0.711, P = 0.106). No difference was observed in sexual function between the two groups (P = 0.351); however, pre-menopausal patients in RATA group had better sexual function than those in RATV group (P = 0.045). Univariate logistic regression analysis showed surgical procedure was not a significant factor for the occurrence of sexual dysfunction. There were no significant difference in DFS (P = 0.845)and OS (P = 0.642) between the two groups. Conclusion Though the postoperative efficacy of the RATA and RATV was equivalent on urinary and sexual function, RATV is an optimal natural orifice specimen extraction for robotic middle rectal cancer resection in women based on anal function.